2019
DOI: 10.1016/j.jamda.2018.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Late-Life Blood Pressure and the Incidence of Cognitive Impairment: A Community-Based Prospective Cohort Study

Abstract: Late-life high blood pressure was independently associated with cognitive impairment in cognitively normal Chinese older adults. Prevention and management of high blood pressure may have substantial benefits for cognition among older adults in view of the high prevalence of hypertension in this rapidly growing population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 31 publications
(47 reference statements)
0
23
1
Order By: Relevance
“…Some researchers found that the increased risk of dementia was related to the increase of SBP in the group under 75 years old [17]. The risk of cognitive impairment increased by 1.17 times when SBP was 130-139 mmHg, however, it increased to 1.54 times when SBP was≥180 mmHg [16]. The results of 3.8-year follow-up of hypertension (n=2800) showed that incidences of MCI and dementia could decrease by 15% in intensive control of blood pressure (SBP<120 mmHg) compared with the standard control group (SB<140 mmHg) (HR = 0.85, 95% CI = 0.74-0.97, P = 0.02) [31]; moreover, statistically significant reduced risk of MCI and dementia can be found in the intensive group (SBP =120 mmHg) less than 75 years old [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers found that the increased risk of dementia was related to the increase of SBP in the group under 75 years old [17]. The risk of cognitive impairment increased by 1.17 times when SBP was 130-139 mmHg, however, it increased to 1.54 times when SBP was≥180 mmHg [16]. The results of 3.8-year follow-up of hypertension (n=2800) showed that incidences of MCI and dementia could decrease by 15% in intensive control of blood pressure (SBP<120 mmHg) compared with the standard control group (SB<140 mmHg) (HR = 0.85, 95% CI = 0.74-0.97, P = 0.02) [31]; moreover, statistically significant reduced risk of MCI and dementia can be found in the intensive group (SBP =120 mmHg) less than 75 years old [32].…”
Section: Discussionmentioning
confidence: 99%
“…For example, some studies have found that hypertension is independently associated with cognitive impairment in later life, the cognitive function declining with increasing SBP, especially SBP ≥ 180mmHg [13][14][15]. In Yuan's study, the cognition declined with the increased SBP like a hockey [16].…”
mentioning
confidence: 99%
“…Some researchers found that the increased risk of dementia was related to the increase of SBP in the group under 75 years old [17]. The risk of cognitive impairment increased by 1.17 times when SBP was 130-139 mmHg, however, it increased to 1.54 times when SBP was≥180 mmHg [16]. The results of 3.8-year follow-up of hypertension (n = 2800) showed that incidences of MCI and dementia could decrease by 15% in intensive control of blood pressure (SBP<120 mmHg) compared with the standard control group (SB<140 mmHg) (HR = 0.85, 95% CI = 0.74-0.97, P = 0.02) [31]; moreover, statistically significant reduced risk of MCI and dementia can be found in the intensive group (SBP = 120 mmHg) less than 75 years old [32].…”
Section: Discussionmentioning
confidence: 99%
“…The total MMSE score ranges from 0 to 30 within 6 dimensions: orientation, registration, attention, language, memory, and visual construction skills. Three methods were used to define cognitive impairment: (1) ≥24, 18-23, and < 18 were used to define normal cognition (reference), mild cognitive impairment and serious cognitive impairment [22,23]; (2) < 18 was used to define cognitive impairment for participants who didn't receive any formal education, < 21 for participants who received 6 years of education or less, and < 25 for participants who received more than 6 years of education [16,24]; (3)≥24 and < 23 were used to define normal cognition (reference) and cognitive impairment [22,23].…”
Section: Assessment Of Cognitive Impairment and Mortalitymentioning
confidence: 99%